Solar Energy Application for Erbil Municipal Wastewater Treatment and Reusing (Journal of Civil Engineering Researchers, 2024)
Up to now, there is no central wastewater treatment plant (WWTP) in Erbil City, Kurdistan Region Iraq. Erbil Municipal waste water (EMWW) discharges directly to the environment, or sometimes it used for irrigation, without treatment. This research focused on the EMWW characteristics, treatment using solar energy technique and reusing. Data were collected from published works since 1994 and visiting the site. Some EMWW quality parameters such as total suspended solids (TSS), chemical oxygen demand (COD), and five day biochemical oxygen demand (BOD5) topped the effluent standards. Accordingly, treatment process like solar energy is essential. Quantity of solar energy in Erbil City is A Unit. Application of solar energy for EMWW treatment led to removal of (80-98) % of BOD, (75-95) % COD, and (85-98) % of TSS. Treaded WW is safe for irrigation. Solar energy can be used for EMWW treatment and it regards as efficient and economic technique.
Keywords: Erbil; Municipal; Solar Energy; Treatment; Wastewater